Contesting Labels: Revisiting Old Questionnaires - Ada, Serhan; Yücel, Şebnem (Cambridge University Press, 2020)
As a response to several questionnaires, manifestos, interviews, and letters that were included in the book Modern Art in the Arab World: Primary Documents, this article carries out a new questionnaire with seven artists form various backgrounds and geographies, in an attempt to update and re-question some of the issues that were highlighted in the collected essays. The questionnaire includes three questions, each focusing on a different issue. The first issue considers the validity of the term “Arab Art,” the second tries to identify the main dynamics of contemporary artistic production, and the last one questions the relation of contemporary production of arts to geography and history. The following interviews have been edited for consistency and clarity.
Keywords: Art market; Arab art; Modern art; Identity; Mediterranean